Encounters With—and Accounting for—Loss: The Wearing of the Past. (June 2016) - Wilkinson, Alex
Loss is problematic: already too much to talk about, it insistently presses upon us the force of its desire. This felt sense of loss, its affective assemblage of the irreducibility of memory and forgetting, attunes us to a deep awareness not of the propriety of our belonging(s) but, rather, to their fragility under the weight of claims to be ours in first place. Loss pulls together scenes, atmospheres, flows, and blockages, liquid assemblages of the individual with queer intersections of time and space. In this sense this article—a mix of literary critique (of Marguerite Duras' La Douleur ), autoethnographic experiment, and photographic practice—is as much a questioning of how loss encodes, in neoliberal society, certain modes of response as sacred, and attempts to find new modes of reframing loss as potency and desire.